Characterizing the Structural Pattern Predicting Medication Response in Herpes Zoster Patients Using Multivoxel Pattern Analysis - Zeng, Ping; Huang, Jiabin; Wu, Songxiong; Qian, Chengrui; Chen, Fuyong; Sun, Wuping; Tao, Wei; Liao, Yuliang; Zhang, Jianing; Yang, Zefan; Zhong, Shaonan; Zhang, Zhiguo; et al. (Frontiers in Neuroscience, 2019)
Herpes zoster (HZ) can cause a blistering skin rash with severe neuropathic pain. Pharmacotherapy is the most common treatment for HZ patients. However, most of these patients are the elderly and immunocompromised, thus often suffering from side effects and easily getting intractable post-herpetic neuralgia (PHN) if medication fails. It is challenging for clinicians to tailor treatment for patients, due to the lack of prognosis information regarding neurological pathogenesis underlying HZ. In the current study, we aimed at characterizing the brain structural pattern of HZ before medication treatment that could help predict medication responses. High-resolution structural magnetic resonance imaging (MRI) scans of 14 right-handed HZ patients (aged 61.0±7.0, 8 males) with poor response and 15 (aged 62.6±8.3, 5 males) age- (p = 0.58), gender-matched (p = 0.20) patients responding well were acquired and analyzed. Multivoxel pattern analysis (MVPA) with searchlight algorithm and support vector machine (SVM) was applied to identify the spatial pattern of gray matter (GM) volume with high predicting accuracy. The predictive regions with accuracy higher than 79% located within the cerebellum, posterior insular cortex (pIC), middle and orbital frontal lobes (mFC, OFC), anterior and middle cingulum (ACC, MCC), precuneus (PCu) and cuneus. Among these regions, mFC, pIC and MCC displayed significant increases of GM volumes in patients with poor response than those with good response. Combination of sMRI and MVPA might be a useful tool to explore the neuroanatomical imaging biomarkers of HZ-related pain associating with medication responses.